1977
DOI: 10.1002/art.1780200202
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between levels of breakdown products of C3, C4, and properdin factor b in synovial fluids from patients with rheumatoid arthritis

Abstract: Synovial fluids from 31 patients with seropositive rheumatoid arthritis (RA) and 23 patients with seronegative RA had significantly increased levels of breakdown products of C3, C4, and properdin factor B when compared to patients with osteoarthritis (OA) ( P < 0.01).The same patients exhibited a considerable overlap of native C3, C4, and properdin factor B levels when their results were compared with those of OA patients. The parallel increase of C3d, C4d, and Ba levels in patients with RA suggests an activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

1979
1979
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 14 publications
2
21
1
Order By: Relevance
“…The results of this study are in substantial agreement with the findings in rheumatoid synovial fluid of the C3 fragments C3c (29,30) and C3d (14, [29][30][31], high proportions of C3d in relation to total C3 (17), and converted forms of C3 (30,32). The degree of C3 conversion in RA joint fluid as detected by antigenantibody crossed electrophoresis has been estimated to exceed 10% in some specimens (33); this is in close accord with our calculated percentage of C3 cleaved Others have found that plasma levels of a C3 fragment (C3d) may correlate with disease activity in RA (31,34,35).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study are in substantial agreement with the findings in rheumatoid synovial fluid of the C3 fragments C3c (29,30) and C3d (14, [29][30][31], high proportions of C3d in relation to total C3 (17), and converted forms of C3 (30,32). The degree of C3 conversion in RA joint fluid as detected by antigenantibody crossed electrophoresis has been estimated to exceed 10% in some specimens (33); this is in close accord with our calculated percentage of C3 cleaved Others have found that plasma levels of a C3 fragment (C3d) may correlate with disease activity in RA (31,34,35).…”
Section: Discussionsupporting
confidence: 90%
“…However, we have found evidence of alternative pathway activation in the lowered levels of factor B and properdin (15) and the control protein factor I (C3b inactivator) (16); others have shown the presence of fragments of factor B in synovial fluid (17) and that RA synovial fluid may activate the alternative pathway directly (18). We did not perform assays for C4dC4ad,,Arg to examine whether classical pathway activation could account for most of the elevated C3dC3ad,,Arg levels, but others have studied metabolic turnover of radiolabeled C4 and factor B in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Study of several typical fluids from each disease group demonstrated that in only some fluids from patients with DJD and SLE there was absolutely no evidence of C3 conversion noted. The greatest conversion to-beta,A was seen in rheumatoid (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Undermentioning
confidence: 99%
“…Measurements of hemolytic complement activity and of individual complement proteins in synovial fluid have been used as investigational tools in studies of the pathogenesis of joint inflammation and have been advocated as useful in the diagnosis of arthritis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The first studies of synovial fluid complement activity in disease observed that to make meaningful comparisons, it was necessary to make a correction for total synovial fluid protein (1,2).…”
mentioning
confidence: 99%
“…Patients with rheumatoid vasculitis have been shown to exhibit somewhat depressed CH50 titers in their sera although CH5O levels in most other RA patients are normal or elevated (13,14). The findings of activation products of C3 and C4 in some RA sera (12,14) have implicated the classical pathway in more widespread disease.…”
mentioning
confidence: 99%